The Role of Biofilm on Microplastics as A Vector for Heavy Metals in the Waters of Sendang Biru, Malang Regency - Al Fatih, Ahmad Nuril Fuad; Kurniawan, Andi; Koentjoro, Maharani Pertiwi (Bogor Agricultural University, Indonesia, 2025)
Microplastic contamination in water provides an ideal surface for biofilm formation. It facilitates other pollutants, such as heavy metals, to attach to their surface. This interaction leads to biological and environmental problems. We tested this phenomenon by investigating the presence of microplastics in water, biofilms on surfaces, and heavy metal accumulation during September 2024. It further examines the relationship between microplastic and their contamination in fish. Samples were collected from two stations, namely Kondang Buntung Fish Auction Place (TPI) and the Indonesian Navy Post, water from Sendang Biru, using a purposive sampling method. A total of 20 liters of water and 6 Banyar fish (Rastrelliger kanagurta) specimens were analyzed. In contrast, biofilm morphology and heavy metal content were analyzed using Scanning Electron Microscopy with energy-dispersive X-ray. The result found that fibre-shaped microplastics, with fragments and filaments, dominated water samples. Microplastics 1-5 mm in size show that their colors included black, blue, red, and transparent. Five biofilm morphologies on the microplastic surfaces were identified: platelet, thin film, solid film, sporous, and diatoms. Heavy metals (Pb, Hg, Cd, Al, Mg, Fe) were detected with weight percentages ranging from 0.473 to 2.533%. Microplastics are found in the digestive tracts of fish, predominantly microplastic as filaments followed by fragments and fibers. We found that biofilm-coated microplastics accumulate heavy metals, posing a risk of pollutant transfer to aquatic organisms.